2013
DOI: 10.1007/s10875-013-9876-3
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of IgG Administered by the Subcutaneous Route

Abstract: PurposeUS licensing studies of subcutaneous IgG (SCIG) calculate dose adjustments necessary to achieve area under the curve (AUC) of serum IgG vs. time on SCIG that is non-inferior to that on intravenous IgG (IVIG), within the FDA-set limit of ±20 %. The results are interpreted as showing that different SCIGs differ in bioavailability. We used three approaches to determine if the bioavailabilities were actually different.MethodsDose adjustments and AUCs from published licensing studies were used to calculate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 23 publications
2
45
0
Order By: Relevance
“…SCIG has reduced bioavailability compared with IVIG, presumably because of decreased absorption in the subcutaneous tissues and increased local IgG catabolism [24]. However, bioavailability does not appear to be determined specifically by the concentration or formulation of the SCIG product [25]. The dosing used in this study achieved steady-state IgG levels that were similar between the two products; only two subjects required dose increases to maintain equivalent IgG levels during treatment with Hizentra.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…SCIG has reduced bioavailability compared with IVIG, presumably because of decreased absorption in the subcutaneous tissues and increased local IgG catabolism [24]. However, bioavailability does not appear to be determined specifically by the concentration or formulation of the SCIG product [25]. The dosing used in this study achieved steady-state IgG levels that were similar between the two products; only two subjects required dose increases to maintain equivalent IgG levels during treatment with Hizentra.…”
Section: Discussionmentioning
confidence: 82%
“…Following screening, eligible subjects received Vivaglobin weekly for 8 weeks followed by Hizentra weekly for 24 weeks, with weeks 9-20 as a transition period and a final 12-week period (weeks [21][22][23][24][25][26][27][28][29][30][31][32]. Study visits took place at screening, entry and at 8, 12, 20 and 32 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…187 If there is preexisting bronchiectasis, there is evidence for using 0.6 g/kg/month. 188 Some practitioners also recommend higher doses (0.6–0.8 g/kg/month) for patients with enteropathy or splenomegaly.…”
Section: Managementmentioning
confidence: 99%
“…37 Higher and more stable trough levels have been seen with the subcutaneous administration of immunoglobulin, alleviating the fatigue and general constitutional symptoms patients have on IVIG toward the end of their 3-4 weeks dosing interval. 25,26,41 However, Berger et al 42 have recently shown that all US-licensed SCIG products have a similar bioavailability: 66.7% ± 1.8% of IVIG. When immunoglobulin is administered via the SC route, the dose is absorbed into the circulation and redistributed to the peripheral tissues more slowly than when given via the IV route.…”
Section: Subcutaneous Immunoglobulin Administration (Scig)mentioning
confidence: 99%